Hemin Promotes Higher Effectiveness of Aminolevulinic-Photodynamic Therapy (ALA-PDT) in A549 Lung Cancer Cell Line by Interrupting ABCG2 Expression - Anantya Pustimbara; Rahma Wirdatul Umami; Nurul Muhammad Prakoso; Anna Rozaliyani; Jamal Zaini; Astari Dwiranti; Shun-ichiro Ogura; Anom Bowolaksono (Medical Sciences, 2024)
Background/Objectives: Due to concerns about drug resistance and side effects, the discovery of improved drugs for lung cancer has attracted studies to find an effective and safe treatment. Aminolevulinic acid-mediated photodynamic therapy (ALA-PDT) is a cancer treatment with minimal side effects. However, ALA-PDT effectiveness can be hindered by ABCG2 and ABCB1 transporters impeding PpIX accumulation. Combining ALA with other substances can enhance PpIX accumulation. Hemin is a potential substance due to its antitumor properties and may be involved in regulating the ABCG2 and ABCB1 expressions. Methods: The objective of this report is to analyze the effects of administering a combination of hemin and ALA after 48 h on A549 lung cancer cells by quantifying cell viability, intracellular PpIX, and ROS accumulation, completed by ABCG2 and ABCB1 expressions. Results: Our data indicate that the combination of hemin and ALA followed by photoirradiation decreased the viability of A549 cells, which was due to increased intracellular PpIX and ROS. The expression of ABCG2 mRNA was significantly decreased after ALA-hemin treatment, while the ABCB1 mRNA expression increased. This result might suggest that ABCG2 plays a greater role than ABCB1 in regulating the PpIX accumulation in A549 lung cancer cells. Conclusions: The combination of ALA and hemin followed by photoirradiation offers a promising novel treatment for lung cancer, and further evaluations of this therapy are required.